Pilot study on LC-MS analysis of bile acids and fatty acids in duodenal content of patients with chronic opisthorchiasis - Kazantseva, Ksenia I.; Sidelnikov, Vladimir S.; Kokova, Darya A.; Frankevich, Vladimir E.; Chagovets, Vitaliy V.; Domracheva, Liubov V.; Mayboroda, Oleg A.; Ivanyuk, Elena E. (Вестник Томского государственного университета. Химия)
We present a pilot study utilizing Liquid Chromatography-Mass Spec-trometry (LC-MS) to analyze bile acids (BA) and fatty acids (FA) in the duodenal content of patients diagnosed with chronic Opisthorchiasis. By using LC-MS analysis, our study aims to shed light on the alterations in bile acids and fatty acids in the duode-nal content, providing insights into the metabolic disruptions caused by chronic opis-thorchiasis. Our correlation analysis demonstrated a clear re-wiring of the BA-FA balance. Notably, the key “hubs” in the fatty acid data, such as nervonic, arachidic, stearic, and linoleic acids, are present in both groups. Our findings highlight the importance of exploring the correlation relationships between metabolic compounds to understand the underlying disruptions in metabolic homeostasis in chronic opisthorchiasis.